The Effect of Foreign Direct Investment, Domestic Investment, and Trade on Economic Growth: Evidence from the Baltic Countries - Yeboah, Evans (Ekonomika, 2025)
This study investigates the impact of foreign direct investment (FDI), domestic investment, and trade on economic growth in the Baltic countries (Estonia, Latvia, and Lithuania). Using annual time-series data from the World Bank for the period 1995–2022, the analysis employs the Pooled Mean Group Autoregressive Distributed Lag (PMG-ARDL) approach. To ensure robustness, the study also applies the fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) methods. The findings reveal that FDI negatively impacts economic growth in the long term, although it has a positive effect in the short term. In contrast, gross fixed capital formation (used as a proxy for domestic investment) positively influences economic growth over the long term but has no significant short-term effect. Domestic savings are found to contribute positively to long-term economic growth, while having a negative impact in the short term. Exports exhibit a negative long-term effect on economic growth, despite their positive short-term impact. The robustness checks using FMOLS and DOLS largely confirm the results obtained from the PMG-ARDL model. Additionally, the causality analysis reveals a unidirectional relationship between economic growth, domestic savings, and FDI. These findings emphasize the importance of considering both the short-term and long-term effects of FDI on economic growth. Policymakers in the Baltic countries are advised to adopt strategic investment policies that balance the benefits and challenges of FDI to address its long-term impacts. The practical implications include the need for targeted policies to promote sustainable economic growth by addressing the dynamic interactions between FDI, domestic investment, and trade.
Keywords: FDI; gross fixed capital formation; GDP per capital; Gross domestic savings; Exports; Baltic